2013
DOI: 10.4103/2211-4122.117982
|View full text |Cite
|
Sign up to set email alerts
|

Indications, utility and appropriateness of echocardiography in outpatient cardiology

Abstract: Objective:Respect of “appropriateness” is considered an essential requirement, both on the clinical and the economic profile, and also as it helps to shorten the waiting list. However, only a few studies have dealt with the control of appropriateness in clinical practice, and most of them have focused only on hospital admissions and invasive procedures.Materials and Methods:INDICARD-out is a prospective, multicenter study carried out by A.R.C.A. (Associazioni Regionali Cardiologi Ambulatoriali) cardiologists f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
1
3
0
1
Order By: Relevance
“…Although we discovered excessive inappropriate ETT from the public healthcare system, inappropriate diagnostic workup was significantly higher from the private healthcare setup. Hypertension was the most common comorbidity among the appropriate ETT referrals, and this outcome was in line with that described in an Italian study by Orsini et al [ 17 ]. The multivariate models demonstrated that only being from a private health setup was an independent predictor of the inappropriate use of ETT.…”
Section: Discussionsupporting
confidence: 90%
“…Although we discovered excessive inappropriate ETT from the public healthcare system, inappropriate diagnostic workup was significantly higher from the private healthcare setup. Hypertension was the most common comorbidity among the appropriate ETT referrals, and this outcome was in line with that described in an Italian study by Orsini et al [ 17 ]. The multivariate models demonstrated that only being from a private health setup was an independent predictor of the inappropriate use of ETT.…”
Section: Discussionsupporting
confidence: 90%
“…Considering the training and clinical backgrounds, data from over 2800 echo prescriptions in Italy showed better guideline‐driven appropriateness in prescriptions made by experts (cardiologists), resulting in more frequent derivation of useful information (63.1% cardiologist vs 46% non‐cardiologist) and consequently more abnormal findings (74.3% vs 55%) 21 . In another analysis including 2110 patients with mean 60.4 years old, to whom echo was mainly prescribed because of hypertension (22%) and screening (16.8%), cardiology training was also associated with higher rates of class I indication, usefulness and pathological features 22 . Thus, it is anticipated that standard echocardiograms ordered by the primary care staff in Brazil—with heterogeneous training background—will likely have suboptimal pretest evaluation, limiting their utility.…”
Section: Discussionmentioning
confidence: 99%
“…21 In another analysis including 2110 patients with mean 60.4 years old, to whom echo was mainly prescribed because of hypertension (22%) and screening (16.8%), cardiology training was also associated with higher rates of class I indication, usefulness and pathological features. 22 Thus, it is anticipated that standard echocardiograms ordered by the primary care staff in Brazil-with heterogeneous training background-will likely have suboptimal pretest evaluation, limiting their utility. This, in addition to the uneven distribution of health resources and test availability in the Brazilian territory (even inside the same state) and to financial crisis, contribute to the current growing waiting lists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graças ao desenvolvimento da tecnologia, a ecocardiografia tem se tornado progressivamente portátil e acessível, passando dos centros de imagem para os locais de atendimento, com potencial para chegar a ambientes não atendidos. 3,4 Portanto, uma abordagem em duas etapas, que inclui a realização do ecocardiograma por não especialistas, seguida de interpretação remota por cardiologistas credenciados, é uma estratégia de rastreamento promissora. 5,6 Isso pode permitir uma alocação de recursos mais eficaz e a implementação de programas de rastreamento mais amplos, permitindo um diagnóstico mais precoce e um tratamento imediato, especialmente onde os recursos são escassos.…”
Section: Introductionunclassified